2012
DOI: 10.1193/1.3675581
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Building Characteristics and Site Conditions on the Damage Distribution in Boumerdès after the 2003 Algeria Earthquake

Abstract: This study highlights the major contributing factors to the observed damage distribution in the city of Boumerdès after the 2003 Algeria earthquake. The results of field investigations and statistical analyses show that a majority of the damaged buildings, mostly mid-rise reinforced concrete (RC) moment-frame systems, were located on steep slopes and small hilltops, along river valleys. The horizontal-to-vertical (H/V) ratios from free-field microtremor measurements at these sites did not show clear results. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…This comparison showed that the theoretical and observed damages are close in the whole of the cases and present a more or less acceptable difference; the results become almost the same if the damage grades 2 and 3 are merged. The origin of the difference between the estimated and observed damages has several causes: adaptation of American capacity and fragility curves to Algerian building typologies, the use of a response spectrum built from the seismic records of free field Keddara station located 12 km from the Boumerdès city, the quality of the expertises and the errors which could be recorded in the damage classification of constructions, the earthquake characteristics, the location of Boumerdès city in the epicentral zone (strong ground motion zone), the poor quality of execution and structural material, lack of structural design, the aftershocks effect reaching a magnitude Mw = 5.8, the buildings orientation effect relatively to the fault (directivity effect), the presence of many flexible stories (Ground floor), as well as the topographic effect in some places close to the rivers crossing the city (Meslem, 2012), etc. These parameters influenced the effective damages suffered by the buildings of the city.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This comparison showed that the theoretical and observed damages are close in the whole of the cases and present a more or less acceptable difference; the results become almost the same if the damage grades 2 and 3 are merged. The origin of the difference between the estimated and observed damages has several causes: adaptation of American capacity and fragility curves to Algerian building typologies, the use of a response spectrum built from the seismic records of free field Keddara station located 12 km from the Boumerdès city, the quality of the expertises and the errors which could be recorded in the damage classification of constructions, the earthquake characteristics, the location of Boumerdès city in the epicentral zone (strong ground motion zone), the poor quality of execution and structural material, lack of structural design, the aftershocks effect reaching a magnitude Mw = 5.8, the buildings orientation effect relatively to the fault (directivity effect), the presence of many flexible stories (Ground floor), as well as the topographic effect in some places close to the rivers crossing the city (Meslem, 2012), etc. These parameters influenced the effective damages suffered by the buildings of the city.…”
Section: Resultsmentioning
confidence: 99%
“…The difference between the observed and estimated damages is also due to the use of American capacity and fragility curves even if a correspondence were made between American and Algerian building typologies. Furthermore, the origin of this difference has also other causes: the elastic response spectrum built from the record signal of Keddara station located at 12 km from Boumerdès site, , the Poor quality of execution and poor quality of structural material, lack of structural design [3] the aftershocks effect reaching a magnitude Mw = 5.8 on 27.05.2003, buildings orientation effect relatively to the fault(directivity effect) (case of Cité Ibn Khaldoun-1200 logements) [27] the presence of many flexible storeys (ground floor) as well as the topographic effect in some places close to the rivers crossing the city (Meslem, 2012). These parameters influenced the effective damages suffered by the buildings in Boumerdès city.…”
Section: Damage Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bendimerad (2004) similarly suggested that retrofitting of already existing vulnerable buildings in seismic prone regions could be considered a long term approach to reduce the losses associated with disasters in the major cities in Algeria. Meslem et al (2012) stated in a post-earthquake investigation that the alarming extent of damages recorded in the Boumerdes 2003 event was attributed to the presence of non-engineered private buildings in the Boumerdes area. Since the existing Algerian seismic code at that time were only applied to public buildings.…”
Section: North Africamentioning
confidence: 99%
“…The May 21, 2003 (Mw 6.8) Zemmouri earthquake caused 2384 deaths and widespread damage of buildings. The observed severe ground motion amplitude was, partly, caused by the lithographical and topographical amplification effects of seismic motion (DLEP 2004;Hellel et al 2010;Dunand et al 2004;Laouami et al 2003;Laouami et al 2006;Meslem et al 2012;Bensalem et al 2010). Worldwide, during the last few decades, liquefaction hazard zonation became among the first steps in each seismic risk analysis and mitigation strategy in urban areas.…”
Section: Introductionmentioning
confidence: 99%